Biology ContributionsInfluence of length of interval between pulses in PDR brachytherapy (PDRBT) on value of Biologically Equivalent Dose (BED) in healthy tissues - Skowronek, Janusz; Malicki, Julian; Zwierzchowski, Grzegorz; Piotrowski, Tomasz (Journal of Contemporary Brachytherapy, 2010)
Purpose: Different PDR treatment schemas are used in clinical practice, however optimal length of interval between pulses still remains unclear. The aim of this work was to compare value of BED doses measured in surrounded healthy tissues according to different intervals between pulses in PDRBT. Influence of doses optimization on BED values was analyzed. Material and methods: Fifty-one patients treated in Greater Poland Cancer Centre were qualified for calculations. Calculations of doses were made in 51 patients with head and neck cancer, brain tumor, breast cancer, sarcoma, penis cancer and rectal cancer. Doses were calculated with the use of PLATO planning system in chosen critical points in surrounded healthy tissues. For all treatment plans the doses were compared using Biologically Equivalent Dose formula. Three interval lengths (1, 2 and 4 hours) between pulses were chosen for calculations. For statistical analysis Friedman ANOVA test and Kendall ratio were used. Results: The median value of BED in chosen critical points in healthy tissues was statistically related to the length of interval between PDR pulses and decreased exponentially with 1 hour interval to 4 hours (Kendall = from 0.48 to 1.0; p = from 0.002 to 0.00001). Conclusions: Prolongation of intervals between pulses in PDR brachytherapy was connected with lower values of BED doses in healthy tissues. It seems that longer intervals between pulses reduced the risk of late complications, but also decreased the tumour control. Furthermore, optimization influenced the increase of doses in healthy tissues.